Writing UNIX device drivers - Pajari, George (Reading, Massachusetts : Addision-Wesley Publishing Company, 1992)
"Writing UNIX Device Drivers" provides application programmers with definitive information on writing device drivers for the UNIX operating system. It explains, through working examples, the issues related to the design and implementation of these important components of application programs. Written by an acknowledged expert, the book uses full source code listings of real devices to explain the underlying concepts.
What is a device driver?; character driver I: a test data generator; character drivers II: an A/D converter; character drivers III: a line printer; block drivers I: a test data generator; Block drivers III: a ram disk driver; block drivers III: a SCSI disk driver; character drivers IV: the raw disk driver; terminal drivers I: the COM1 port; character drivers V: a tape drive; Streams drivers I: a loop-back driver; streams drivers II: the COM1 port; driver installation; zen and the art of device driver writing; writing drivers for system V release 4; index.
Includes bibliographical references and index.
Keywords: OPERATIONAL SYSTEM